2009
DOI: 10.1128/cmr.00036-08
|View full text |Cite
|
Sign up to set email alerts
|

AmpC β-Lactamases

Abstract: SUMMARY AmpC β-lactamases are clinically important cephalosporinases encoded on the chromosomes of many of the Enterobacteriaceae and a few other organisms, where they mediate resistance to cephalothin, cefazolin, cefoxitin, most penicillins, and β-lactamase inhibitor-β-lactam combinations. In many bacteria, AmpC enzymes are inducible and can be expressed at high levels by mutation. Overexpression confers resistance to broad-spectrum cephalosporins including cefotaxime, ceftazidime, and ceftr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
1,697
10
76

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,823 publications
(1,868 citation statements)
references
References 351 publications
(207 reference statements)
30
1,697
10
76
Order By: Relevance
“…Acinetobacter inherently produces chromosomally mediated AmpC type cephalosporinases which are also known as Acinetobacter derived cephalosporinases (ADCs), which mediate resistance to cephalothin, cefazolin, cefoxitin, most of the penicillins and β-lactamase inhibitor β-lactam combinations. More than 25 varieties of AmpC β-lactamases that share ≥ 94% protein sequences have been described for Acinetobacter spp [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acinetobacter inherently produces chromosomally mediated AmpC type cephalosporinases which are also known as Acinetobacter derived cephalosporinases (ADCs), which mediate resistance to cephalothin, cefazolin, cefoxitin, most of the penicillins and β-lactamase inhibitor β-lactam combinations. More than 25 varieties of AmpC β-lactamases that share ≥ 94% protein sequences have been described for Acinetobacter spp [4].…”
Section: Introductionmentioning
confidence: 99%
“…Acinetobacter inherently produces chromosomally mediated AmpC type cephalosporinases which are also known as Acinetobacter derived cephalosporinases (ADCs), which mediate resistance to cephalothin, cefazolin, cefoxitin, most of the penicillins and β-lactamase inhibitor β-lactam combinations. More than 25 varieties of AmpC β-lactamases that share ≥ 94% protein sequences have been described for Acinetobacter spp [4].PER-1 was the first ESBL to be reported in A. baumannii and strains harbouring PER-1 demonstrate a high level resistance to penicillins and extended spectrum cephalosporins, but it fortunately does not confer resistance to carbapenems. Routine detection of strains harbouring ESBLs may be difficult, because the synergy existent between third-generation cephalosporins and clavulanic acid, which is typically observed with ESBL-producing Enterobacteriaceae, which tends to be minimal with Acinetobacter spp.…”
mentioning
confidence: 99%
“…Automated resistance analysis with the VITEK 2 system revealed increased MIC values to the carbapenems meropenem (8 mg/L) and imipenem (8 mg/L), which were subsequently confirmed by Etests. Imipenem Etests on MHA with or without 250 mg/L cloxacillin revealed that imipenem resistance was significantly reduced in the presence of cloxacillin, which is an inhibitor of β-lactamases of the AmpC-type [17]. Specifically, the MIC was reduced to 0.125 mg/L (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Al igual que para E. coli y K. pneumoniae productores de BLEE, los carbapenems son la primera opción terapéutica para infecciones graves causadas por bacterias productoras de AmpC (25). La resistencia de Enterobacteriaceae a carbapenems es muy inusual, menor de 5% en nuestro estudio, y se reporta ya que es importante en el tratamiento de infecciones producidas por bacterias multirresistentes y por ser un marcador para la aparición de carbapenemasas, especialmente de la KPC (Klebsiella pneumoniae carbapenemase) en nuestro país (10,26).…”
Section: Discussionunclassified